Meeting the challenges of web application development: the web engineering approach - Murugesan, San; Deshpande, Yogesh (Proceedings of the 24th International Conference on Software Engineering, 2002)
The Web has very rapidly become central to many applications in diverse areas. As our reliance on Web-based applications continues to increase and the Web systems supporting these applications become more complex, there is growing concern about the manner in which the Web-based systems/applications are created and their quality, integrity and maintainability. The development of Web-based systems has generally been ad hoc, resulting in poor quality and maintainability. In the recent times, there have been many failures of Web applications due to a variety of problems and causes. The way the developers address these problems is critical to deploying successful large-scale Web applications.This tutorial addresses these issues and offers a holistic approach to managing the complexity of development of Web-based systems and Web applications. It highlights the various real-world issues, challenges and considerations in development of large Web applications, compared to traditional software development, and recommends the Web engineering approach that Web/software developers could follow.Web engineering deals with systematic, disciplined and quantifiable approaches to development, operation, and maintenance of Web-based systems and applications [1-9]. It embodies engineering principles and practices to Web application and Web site development and draws on software engineering and a number of contributing disciplines.Specifically, the tutorial aims to:* Highlight the problems, complexity and challenges of Web application development relative to software development* Offer a holistic approach to development of Web applications* Present Web development methodologies and processes* Address the issues of scalability, maintainability, usability, configuration management and other non-technical aspects* Recommend suitable Web testing and quality assurance approaches* Discuss project management issues specific to Web developmentThis tutorial is specifically targeted to address the needs of a growing community of software practitioners, Web application developers, project managers IT and business professionals, ecommerce system implementers, academics, researchers and students.